Interculturality in health: reflections from an indigenous experience in the Peruvian Amazon - Cárdenas, Cynthia Giovanna (2017)
This article examines the main characteristics of the proposal on interculturality developed by an indigenous Amazonian organization of Peru for the training of indigenous youth as nurse technicians in intercultural health. It shows how the Interethnic Association for the Development of the Peruvian Jungle (Aidesep) appropriates the concept of interculturality, reconfigures and reconstructs it. Based on internal documents, institutional publications, testimonies of graduates of the intercultural health program, leaders and members of the technical team of the Indigenous Health Program of AIDESEP, we analyze the construction and implementation of the concept of interculturality. We also examin the way in which an indigenous organization becomes a proponent of interculturality, building an indigenous response for the training of health professionals prepared to provide culturally appropriate health services to the indigenous population. The proposal for the training of nurse technicians in intercultural health shows that it is possible for critical interculturality to move from discourse to practice when indigenous peoples develop their own intercultural proposals.